Self-concept, self-esteem and academic achievement: Strategies for maintaining self-esteem in students experiencing academic failure - Peixoto, Francisco José Brito (2010)
Previous research into the relationship between self-esteem and academic achievement shows that despite differences in academic self-evaluation, students’ global self-representations do not differ as a result of their grades at school. In this study, we will analyse the strategies that underachievers used to maintain their self-esteem at an acceptable level. The participants were 955 adolescents in the 7th, 9th and 11th grades at four secondary schools in Lisbon. Three hundred fifty-two of these students had retaken a year at least once in their school careers, whilst 603 had never done so. We collected the data using both a self-concept scale and a scale for evaluating attitudes towards school. Results show that self-esteem is maintained through positive self-representations in non-academic facets of self-concept and/or by devaluing school-related competences. They also show that younger students are less likely to maintain self-esteem by devaluing the school experience.